Openness and topic avoidance in interpersonal communication about ovarian cancer: An uncertainty management perspective - Dinah A. Tetteh; Najma Akhther (Qualitative Research in Medicine & Healthcare, 2022)
This study examined openness and topic avoidance in interpersonal communication about ovarian cancer. Guided by the uncertainty management theory, the researchers analyzed qualitative data from 28 ovarian cancer patients/survivors and found openness and topic avoidance to be complex communication behaviors which are connected to patients/survivors’ uncertainty. Participants appraised uncertainty about disease prognosis and effectiveness of treatments as a threat; thus, they avoided topics such as treatment side effects and fears about death and disease recurrence to manage such uncertainty. Furthermore, findings showed that communication about ovarian cancer is layered with degrees of openness and avoidance relative to respective audiences and changing illness trajectories. Overall, the findings indicate connections between interpersonal communication about ovarian cancer and uncertainty management practices, suggesting that intervention efforts should help cancer patients/survivors and relational others practice sensitivity when discussing topics such as death and dying.